Global distribution of grid connected electrical energy storage systems - Katja Buss; Patrick Wrobel; Christian Doetsch (International Journal of Sustainable Energy Planning and Management, 2016)
This article gives an overview of grid connected electrical energy storage systems worldwide, based on public available data. Technologies considered in this study are pumped hydroelectric energy storage (PHES), compressed air energy storage (CAES), sodium-sulfur batteries (NaS), lead-acid batteries, redox-flow batteries, nickel-cadmium batteries (NiCd) and lithium-ion batteries. As the research indicates, the worldwide installed capacity of grid connected electrical energy storage systems is approximately 154 GW. This corresponds to a share of 5.5 % of the worldwide installed generation capacity. Furthermore, the article gives an overview of the historical development of installed and used storage systems worldwide. Subsequently, the focus is on each considered technology concerning the current storage size, number of plants and location. In summary it can be stated, PHES is the most commonly used technology worldwide, whereas electrochemical technologies are increasingly gaining in importance. Regarding the distribution of grid connected storage systems reveals the share of installed storage capacity is in Europe and Eastern Asia twice as high as in North America.